Virion Structure of Black Queen Cell Virus, a Common Honeybee Pathogen - Spurny, Radovan; Přidal, Antonín; Pálková, Lenka; Kiem, Hoa Khanh Tran; de Miranda, Joachim R; Plevka, Pavel (Journal of virology, 2017)
Viral diseases are a major threat to honeybee (Apis mellifera) populations worldwide and therefore an important factor in reliable crop pollination and food security. Black queen cell virus (BQCV) is the etiological agent of a fatal disease of honeybee queen larvae and pupae. The virus belongs to the genus Triatovirus from the family Dicistroviridae, which is part of the order Picornavirales Here we present a crystal structure of BQCV determined to a resolution of 3.4 Å. The virion is formed by 60 copies of each of the major capsid proteins VP1, VP2, and VP3; however, there is no density corresponding to a 75-residue-long minor capsid protein VP4 encoded by the BQCV genome. We show that the VP4 subunits are present in the crystallized virions that are infectious. This aspect of the BQCV virion is similar to that of the previously characterized triatoma virus and supports the recent establishment of the separate genus Triatovirus within the family Dicistroviridae The C terminus of VP1 and CD loops of capsid proteins VP1 and VP3 of BQCV form 34-Å-tall finger-like protrusions at the virion surface. The protrusions are larger than those of related dicistroviruses.IMPORTANCE The western honeybee is the most important pollinator of all, and it is required to sustain the agricultural production and biodiversity of wild flowering plants. However, honeybee populations worldwide are suffering from virus infections that cause colony losses. One of the most common, and least known, honeybee pathogens is black queen cell virus (BQCV), which at high titers causes queen larvae and pupae to turn black and die. Here we present the three-dimensional virion structure of BQCV, determined by X-ray crystallography. The structure of BQCV reveals large protrusions on the virion surface. Capsid protein VP1 of BQCV does not contain a hydrophobic pocket. Therefore, the BQCV virion structure provides evidence that capsid-binding antiviral compounds that can prevent the replication of vertebrate picornaviruses may be ineffective against honeybee virus infections.
Keywords: Dicistroviridae; virus; krystalografie rentgenová; Picornavirales; Bees; insect disease; X ray; X-ray crystallography; Capsid Proteins; včely; virové plášťové proteiny; virion; molekulární modely; Crystallography, X-Ray; capsid; Models, Molecular; honey bee; crystallography; Animals; Virion; konformace proteinů; Triatovirus; zvířata; Apis mellifera; structure; Cripavirus; honeybee; Viral Structures; Protein Conformation; virové struktury